DO KEY OPINION LEADERS (KOL) MATTER IN DIGITALLY MARKETED BEAUTY PRODUCTS? THE IMPACT OF KOL ON TIKTOK - Sembel, Jacquelinda Sandra; Putri, Derinda Alika (Milestone: Journal of Strategic Management, 2024)
In the era of digital marketing, the role of Key Opinion Leaders (KOL) has become critical to attract new customers. However, previous studies reveal inconsistent results.  This study aims to investigate the influence of Key Opinion Leaders (KOL) on purchasing interest in cosmetics products. The study employs a descriptive quantitative method, using a survey questionnaire distributed to 200 respondents. The respondents have TikTok accounts and follow Key Opinion Leaders in the beauty sector on TikTok. The research employs a quantitative study with a survey questionnaire. Data was analyzed using SmartPLS 4 software. The study reveals interesting results. First, there is a positive influence of KOL Expertise on followers' buying interest. However, KOL Attractiveness and Trustworthiness do not have a positive influence on followers' buying interest. The research findings provide strategic implications for marketers and business owners who plan to optimize their digital marketing strategies by employing Key Opinion Leaders.